Yannis Tzitzikas and Yannis Marketakis: Cinderella’s Stick – A Fairy Tale for Digital Preservation - Tsakonas, Giannis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
We present a critical review of the following book on digital preservation: Cinderella’s Stick – A Fairy Tale for Digital Preservation, by Yannis Tzitzikas and Yannis Marketakis. Basingstoke, UK: Springer Nature, 2018, XXI, 249p. 97 b/w illus., 13 illus. in colour Hardcover, ISBN 978-3-319-98487-2; e-Book, ISBN 978-3-319-98488-9 The book exploits a storytelling technique of the classic fairy tale in order to convey more easily the very technical issues of the field.